Regional trade and development strategies in the era of globalization - Prabhakar, Akhilesh Chandra; Kaur, Gurpreet, 1988-; Erokhin, Vasily, 1980- (Advances in finance, accounting, and economics (AFAE) book series., 2020)
"This book examines the theoretical and practical trends of regional trade and development in the era of globalization"--